2016
DOI: 10.4236/psych.2016.77104
|View full text |Cite
|
Sign up to set email alerts
|

Pretty Face Matters: Relative Importance of the Face and Body Attractiveness in China

Abstract: This study gauges the relative importance of face and body attractiveness in terms of physical attractiveness in China. In the study of attitude, 653 participants were asked to prioritize face and body attractiveness in two mating contexts (short-term vs. long-term) via a survey. In the study of behavior, 232 participants were initially asked to remove either "face box" or "body box", and were afterwards shown images of 10 individuals of opposite sex and rated face, body and combined attractiveness of each ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(23 reference statements)
0
2
1
Order By: Relevance
“…This is consistent with the earlier findings when asked regarding the type of advertisement that affects them the most. However, this finding is contradictory to findings in previous studies which suggested facial attractiveness to be more important than physical attractiveness for body image (Currie & Little, 2009;Rau, Gong, & Zhuang, 2016).…”
Section: Emerging Adults' Behavioral Responses Towards Media Advertisingcontrasting
confidence: 99%
“…This is consistent with the earlier findings when asked regarding the type of advertisement that affects them the most. However, this finding is contradictory to findings in previous studies which suggested facial attractiveness to be more important than physical attractiveness for body image (Currie & Little, 2009;Rau, Gong, & Zhuang, 2016).…”
Section: Emerging Adults' Behavioral Responses Towards Media Advertisingcontrasting
confidence: 99%
“…Cross‐cultural research indicated that the body contributed more to the beauty ideal in Western culture, while the face contributed more to the beauty ideal in Asian culture (Frith, Shaw, & Cheng, ). Studies in China have also indicated that individuals typically give a higher priority to facial attractiveness than bodily attractiveness (Rau et al, ), and that young adults are more dissatisfied with facial appearance than fatness (Chen et al, ). These results indicate that the beauty ideal is more related to the face than the body in the Chinese cultural context.…”
Section: Limitations and Prospective Researchmentioning
confidence: 99%
“…According to evolutionary theory, we may observe a general attentional bias to female faces. As Chinese individuals may focus more on face attractiveness than body attractiveness (Chen, Jackson, & Huang, ; Rau, Gong, & Zhuang, ), they are suitable subjects for examining the effect of facial attractiveness on attentional bias. To the best of our knowledge, this study is the first to examine the attentional bias of DD patients to faces with different attractiveness, which may provide important evidence for the cognitive–behavioral model in information processing.…”
mentioning
confidence: 99%